Mycobacterium avium subsp paratuberculosis detection from blood of Crohn's disease patients in a portuguese hospital - Martinho, António (2012)
Mycobacterium avium subsp paratuberculosis (MAP) has been associated with Crohn’s disease (CD). We performed MAP DNA detection in the blood of controls and CD patients followed at Hospital de São João, by IS900-based nested PCR. We found that 60% (6 out of 10) of CD patients were positive for MAP DNA, against 38% (8 out of 21) of control subjects. MAP detection in CD patients will allow us to correlate MAP infection with different pathological and immunological patterns of the disease. Mycobacterium avium subsp paratuberculosis (MAP) tem vindo a ser associada com a doença de Crohn (CD). Neste trabalho realizamos a detecção por nested PCR de DNA de MAP, no sangue de controlos e de doentes com CD seguidos no Hospital de São João. Detectámos seis (em 10) pacientes positivos para DNA de MAP (60%), e sete (em 20) controlos positivos (35%). A detecção de MAP em doentes com CD permitirá estudar possíveis correlações entre a infecção por MAP e diferentes características patológicas e imunológicas da CD.